Enhancing Organizational Resilience through Crisis Management Strategies: A Case Study Approach - Benardi Benardi; Grace Yulianti; Mohammad Chaidir (LPPM STIE Kasih Bangsa, 2024)
In today's dynamic and uncertain business environment, organizational resilience is imperative for survival and sustained success. This research investigates how crisis management strategies contribute to enhancing organizational resilience. Utilizing a case study approach, we examine real-world instances where organizations effectively navigated crises to emerge stronger. Through qualitative analysis of diverse industries, we identify commonalities and best practices in crisis response and recovery. Findings underscore the significance of proactive planning, robust communication channels, adaptive leadership, and resource allocation in bolstering resilience. Moreover, the study sheds light on the role of organizational culture in fostering resilience amidst adversity. Insights gleaned from this research provide practical implications for leaders and managers seeking to fortify their organizations against unforeseen disruptions, ultimately contributing to the advancement of organizational resilience theory and practice.